2013
DOI: 10.1016/j.jviromet.2013.04.018
|View full text |Cite
|
Sign up to set email alerts
|

HPV Direct Flow CHIP: A new human papillomavirus genotyping method based on direct PCR from crude-cell extracts

Abstract: HPV Direct Flow CHIP is a newly developed test for identifying 18 high-risk and 18 low-risk human papillomavirus (HPV) genotypes. It is based on direct PCR from crude-cell extracts, automatic flow-through hybridization, and colorimetric detection. The aim of this study was to evaluate the performance of HPV Direct Flow CHIP in the analysis of 947 samples from routine cervical screening or the follow-up of abnormal Pap smears. The specimens were dry swab samples, liquid-based cytology samples, or formalin-fixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 38 publications
3
22
0
2
Order By: Relevance
“…The overall positive rates and the concordance rate of the two assays were comparable to those of previous reports [4][5][6][7][8][9][10][11]. The positive rates of individual genotypes were relatively higher in GenoBlot than in HPVDNAChip, with exceptions for genotypes 51 and 56, for which HPVDNAChip showed higher positive rates than GenoBlot.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The overall positive rates and the concordance rate of the two assays were comparable to those of previous reports [4][5][6][7][8][9][10][11]. The positive rates of individual genotypes were relatively higher in GenoBlot than in HPVDNAChip, with exceptions for genotypes 51 and 56, for which HPVDNAChip showed higher positive rates than GenoBlot.…”
Section: Discussionsupporting
confidence: 86%
“…In current practice, there are three major contexts in which tests for high risk (HR) genotypes of HPV are relevant: 1) primary screening of cervical cancer and precancerous lesions; 2) triage of low-grade disease; and 3) test of cure after treatment [2,3]. A significant number of studies have been reported for the primary cervical high risk lesion screen and triage; however, little has been reported in terms of the evaluation of test of cure [2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Based on their association with different grades of lesions, HPV that can induce carcinogenesis has been classified as high risk or oncogenic, while low-risk HPVs are those which cause genital warts and collaborate with high-risk HPVs. The HPV Direct Flow CHIP is intended for the simultaneous screening and genotyping of 18 high-risk genotypes (HPV16, 18, 26, 31, 33, 35, 39, 45, 51, 52, 53, 56, 58, 59, 66, 68, 73, and 82) and 4 low-risk genotypes (HPV6, 11, 42, and 44/45) by PCR, followed by reverse dot-blot hybridization that is based on DNA flow technology (semi-automated hybriSpot 12 TM and automated hybriSpot 24 TM ) [16] . Finally, descriptive statistics were used to determine the distribution of HPV.…”
Section: Genotyping Of Hpvmentioning
confidence: 99%
“…The average global prevalence of HPV infection has been reported to be almost 10% (in the range of 1.4-25.6%). This group of viruses consists of low-risk HPVs that do not cause cancer but can cause skin warts (genotypes 6, 11, 42, and 44), and high-risk HPVs that cause cancer (genotypes 16,18,26,31,33,35,39,45, 51, 52, 53, 56, 58, 59, 66, 68, 73, 82). Neoplastic and cervical cancer may occur due to exposure to high-risk HPV infection.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of HPV Direct Flow CHIP in cytological samples was found to be highly similar to that of the Linear Array Genotyping Test (Roche Molecular Systems, Alameda, CA, USA), Hybrid Capture 2 (Digene Corp., Gaithersburg, MD, USA), and CLART HPV2 (Genomica, Tres Cantos, Madrid, Spain) commercial assays, by Direct PCR (using crude cell extracts) [7]. In addition, a high agreement was observed among the results of HPV Direct Flow CHIP, Linear Array Genotyping Test, and Direct Sequencing when purified DNA was used as amplification template (submitted for publication).…”
Section: Introductionmentioning
confidence: 99%